Groundwater non-carcinogenic health risk comprehensive assessment based on DLAFVRT model in an island city. (April 2023) - Huang, Yong; Wang, Daqing; Cheng, Zijian; Xu, Haoli; Ding, Zhibin; Lu, Zhao; Cui, Huiru; Qian, Kun
Graphical abstract: Highlights: A novel groundwater health risk assessment method combined Modflow, RS and GIS. The DLAFVRT model was constructed based on GIS technology. Construct a simple human health risk assessment model using MT3DMS, AHP and GIS. Provide a theoretical basis for the rational allocation of groundwater resources. Abstract: The long-term leakage of surface contaminants can severely affect the quality of shallow groundwater, thereby significantly affecting human health. This paper analyzed the spatial variations in groundwater non-carcinogenic health risk on the west coast of the Wailingding Island. A novel method for groundwater health risk assessment combining Modflow, remote sensing, and geographic information system (GIS) data was proposed. The DLAFVRT model, which included seven indicators: Groundwater depth (D), Land-use type (L), Aquifer medium (A), Fracture (F), Vegetation coverage (V), Net recharge (R) and Terrain slope (T), and potential non-carcinogenic health risk were based on the groundwater flow field and pollutant transport model constructed by Modflow and MT3DMS. The analytic hierarchy process was used to determine the weight of each index and optimize the model. Finally, the two evaluation results were superimposed to obtain a comprehensive evaluation of the groundwater health risk. The health risk zoning map showed that in the study area, the heavy-risk area accounted for 16.83%, high-risk area accounted for 26.45%, medium-risk area accounted for 42.25%, and low-risk area accounted for 14.47%. Moreover, approximately half of the areas were rated as high-risk or above, indicating that groundwater is susceptible to surface pollutants. Based on the groundwater numerical simulations, the multi-index groundwater health risk comprehensive evaluation system developed by combining groundwater vulnerability and human health risk provides a theoretical reference basis for the scientific management and rational allocation of groundwater resources.